The situation of social farms and the theoretical frameworks - Bazsik, István (Studia Mundi – Economica, 2022)
The social farm system in our country is in its infancy. Although the first social farms were set up in the early 2000s with government support, they are still not accessible to a wider target group. Education, social inclusion, reintegration, and the preservation and improvement of physical and mental health, as well as recruitment for agricultural training are tasks of which the social farm is one of, if not the best form, despite this there is hardly any access to such services in Hungary, as there are hardly any such farms in the country. The target groups concerned are the disadvantaged, the addicted, the mentally and/or physically handicapped, the criminal record seeking integration, and last but not least children and the elderly. In the last ten to fifteen years, several social farm initiatives have been launched independently of each other, with different target groups, but the number of social farms today is less than 50, and many of them are not necessarily farms. In our country, care farms, therapeutic gardens and, in some cases, community gardens, are typical single-purpose (social and/or health-oriented) farms run mainly by NGOs and structured to fulfil certain functions. This single-purpose character is evident in several aspects of the initiatives taken in this country.- There is an exclusive focus on specific target groups (autistic people, Roma inclusion, reintegration of the unemployed). (this limits the successful implementation of inclusion and integration)- The primacy, sometimes exclusivity, of the social function as an operational objective.- Multifunctionality of agricultural functions and objectives (no or limited real production).- The establishment of therapeutic and care farms and functions which are very different from those of farm management.- An idealised, sometimes naive, approach to agro-industrial functions.Therefore, it is necessary to rethink which farm form is capable of playing an active social role in addition to its primary agricultural profile within multifunctional agriculture. Such an organisation may be able to serve social objectives primarily relevant to agriculture, such as agricultural reproduction and environmental education, rural development, raising the sector's social profile, disseminating basic agricultural knowledge, education, traditional preservation, gene conservation and diversification. However, this also requires a rethinking of the conceptual framework, so that agricultural enterprises which are also willing to provide social farm services can be defined according to their main profile and thus supported by appropriate funding.  The research seeks to answer these questions and to provide answers to the place and role of social farms.